Jellyfish (Scyphozoa and Hydrozoa) as natural environmental DNA samplers: a case study in the Northern Adriatic sea - C. May; A. V. Cunnington; P. Shum; M. Avian; V. Tirelli; G. Motta; S. Mariani; C. S. Wilding (Marine Biology, 2026)
Conservation management, aimed at mitigating the ongoing biodiversity loss, critically relies on ecosystem monitoring to enable accurate estimates of species distributions and population sizes. Environmental DNA (eDNA) analysis has become increasingly popular for non-invasive and high-throughput species assessment, including fish species diversity. Beyond the established sample collection protocols, natural samplers of eDNA (nsDNA) – organisms that trap environmental genetic material in their tissues – show considerable promise, with recent work especially demonstrating the remarkable effectiveness of sea sponges. Here, the potential of jellyfish (phylum Cnidaria) to serve as motile, marine, pelagic natural samplers of eDNA was investigated through DNA metabarcoding using fish specific primers. Jellyfish are opportunistic marine predators known to consume fish eggs and larvae and their presence has been associated with certain fish species, making them potentially useful for open water fish assessment. Four species, the many-ribbed jellyfish ( Aequorea forskalea , Class Hydrozoa), the moon jelly ( Aurelia solida , Class Scyphozoa, Order Semaeostomeae), the barrel jellyfish ( Rhizostoma pulmo Class Scyphozoa, Order Rhizostomeae) and the fried-egg jellyfish Cotylorhiza tuberculata (Class Scyphozoa, Order Rhizostomeae) were collected from the Italian waters of the Gulf of Trieste (northern Adriatic Sea) and nsDNA isolated, sequenced and analysed. Across all species, 28 fish Molecular Operational Taxonomic Units (MOTUs) were detected including pelagic species, benthic species likely spawning at the time of sampling, and species known to associate with the presence of jellyfish. We highlight the potential of jellyfish as tools for enhancing biodiversity monitoring, particularly in remote and inaccessible areas where conventional surveys may be difficult to employ.